ChemInform Abstract: Reactions of α‐Ylidene (Vinylidene, Benzylidene, Styrylmethylidene) Bis[carbonyls] with Copper Mono/Bis[carbonylcarbenoids]. - Merey, Goekce; Kaya, Mustafa; Anac, Olcay (Wiley, 2013)
AbstractThe product distribution of the copper‐catalyzed reaction of various conjugated dicarbonyl compounds with either diazomalonate (II) or diazoacetate (XII) are studied (40 examples).